Radar Analysis (Competancy Gap Analysis) – Analytical Study Of Employees Competency Level - NITHYA, N.; ANJANI, P.K. (The journal of contemporary issues in business and government, 2021)
Competency mapping is one of the sought after term in the domain of HR irrespective of the nature of the organization. The term competency mapping has always taken as an important factor because of its analytical nature in assessing the employability level of workers. Though the nature of job and the job description varies, the technique of understanding the need between whatemployees possess and what the organization want from an employee always stay evergreen. Keeping this as an objective, the present study attempted to find the competency gap analysis among 150 employees of a private manufacturing organization located in Tamilnadu, India. The study implemented the Radar analysis to measure the competency gap and also the same was done for assessing selective skill set of the employees. The present study found a very less gap between the expected and actual competency of employees which infers that the present organization has competent employees and they are also found to be less deviating from the expected competency which can be eliminated by organizing training needs.